4QSamuela and the text of Samuel - Driesbach, Jason K. (Vetus Testamentum, Supplements, 2016)
In 4QSamuelᵃ and the Text of Samuel, Jason Driesbach offers a thorough analysis of secondary readings in 4QSamuelᵃ (4Q51) along with those in other major witnesses to Samuel (MT, Gᴮ, Gᴸ), leading to a nuanced characterization of the scribal features and textual affiliation of 4QSamuelᵃ, with implications for understanding its place in text-critical studies and literary analyses of the books of Samuel. 4QSamuelᵃ has been regarded by some scholars as an untrustworthy witness to the text of Samuel and by other scholars as a crucial witness, sometimes containing lost readings. Further, some regard this scroll as a non-biblical work based on Samuel. Driesbach's analysis offers an evaluation of these views based on a sound and thorough consideration of the scroll.